Assessment of the safety and probiotic characteristics of Lactobacillus salivarius CGMCC20700 based on whole-genome sequencing and phenotypic analysis - Jiang, Yu-Hang; Yang, Rui-Si; Lin, Yi-Cen; Xin, Wei-Gang; Zhou, Huan-Yu; Wang, Feng; Zhang, Qi-Lin; Lin, Lian-Bing (Frontiers in Microbiology, 2023)
Lactic acid bacteria are generally regarded as alternatives to antibiotics in livestock and poultry farming, especially Lactobacillus strains, which are safe and have probiotic potential. Although Lactobacillus salivarius has long been proposed to be a probiotic, the understanding of the roles of this species is still in its infancy. Here, a strain of L. salivarius CGMCC20700 isolated from the intestinal mucosa of Yunnan black-bone chicken broilers was investigated in the context of its safety and probiotic characteristics by whole-genome sequencing in parallel with phenotypic analysis. Whole-genome sequencing results showed that L. salivarius CGMCC20700 has a single scaffold of 1,737,577 bp with an average guanine-to-cytosine (GC) ratio of 33.51% and 1,757 protein-coding genes. The annotation of Clusters of Orthologous Groups (COG) classified the predicted proteins from the assembled genome as possessing cellular, metabolic, and information-related functions. Sequences related to risk assessment, such as antibiotic resistance and virulence genes, were identified, and the strain was further confirmed as safe according to the results of antibiotic resistance, hemolytic, and acute oral toxicology tests. Two gene clusters of antibacterial compounds and broad-spectrum antimicrobial activity were identified using genome mining tools and antibacterial spectrum tests. Stress resistance genes, active stressor removal genes, and adhesion related genes that were identified and examined with various phenotypic assays (such as stress tolerance tests in acids and bile salts and auto aggregation and hydrophobicity assays). The strain showed a high survival rate in the presence of bile salts and under acidic conditions and exhibited significant auto aggregation capacity and hydrophobicity. Overall, L. salivarius CGMCC20700 demonstrated excellent safety and probiotic potential at both the genomic and physiological levels and can be considered an appropriate candidate probiotic for livestock and poultry farming.